Effect of Advertising on Employee Turnover Intention: - Takumi Kato; Ryosuke Ikeda; Masaki Koizumi (Maketingu Janaru, 2023)
Since internal marketing (IM) treats employees as customers, the focus has naturally been on internal measures. However, consumer-oriented advertising provides an opportunity for employees to recognize the social impact of their work and change their mindset. Such activities can be seen in business, but knowledge based on academic research is scarce. Therefore, this study examined the effects on job satisfaction and turnover intention by targeting ten factors, including advertising and nine factors covered in existing IM literature (capability acquisition, wages, work-life balance, relationship with superiors, diversity of human resources, office facilities, cafeteria, advanced technology, and purpose). An online survey of 5,000 full-time employees across ten industries (automotives, electronics, medical equipment, food, real estate, information technology, finance, retail, service, and government) was conducted in Japan. Advertisement had no effect on satisfaction, but had a significant positive effect on turnover intention. Furthermore, we found that the smaller the size of the company and the younger the employees, the more likely the employees are to change jobs. This result indicates the need to take care not to increase the desire to change jobs when promoting internal communication through advertisements.